Effect of Eugenia caryophyllus clove essential oil and its active ingredients on the growth of a number of Cram-positive and negative bacteria - Muthana Mohammed; Omer Ramadan; Ragheed Ghazal (College of Education for Pure Sciences, 2006)
In this study, the essential oil was isolated from dried flower buds of Eugenia caiyophyllus (clove), then the eugenol and the acidic compounds were isolated from the essential oil. The inhibiting effect of these compounds were investigated on growth of some bacteria which are: Bacillus subtilis, Staphyhcoccus aureus, Pseudomonas aenighiosa> Escherichla coli Proteus mirabilis and Salmonella typhi. The steam distillation was used to isolate the essential oil while the chemically active extraction was used to isolate eugenol and neutral compounds. The eugenol was identificated by Thin layer chromatography (TLC) plate and determination the Rate of flow (Rf) of it. The essential oil showed better inhibiting effect on the all bacteria which was used in this study compared to commercial antibiotics as a control. Also, eugenol was showed an inhibiting effect on the all bacteria which was compared to commercial antibiotics but it's effect was stronger than the effect of essential oil. The neutral compounds have no effect on Ps. aeruginosa and Prof, mirabilis., but have an inhibiting effect which are less than that indicated for essential oil and eugenol compound compared to a control (Augmentin and Ciprofloxacin).